(untitled) (Journal of the College of Basic Education, 2023)
The knowledge of the abrogated and the abrogated is one of the important sciences of the Qur’an, and the scholars have stipulated the importance of knowing this science for everyone who wants to interpret the Qur’an or search for its rulings. Ali, may God be pleased with him, storyteller: Do you know the transcriber and the abrogated? He said: God knows best. He said: I perished and perished (). Many have written about it () and I will talk in this topic about the definition of abrogation, its wisdom, what abrogation occurs, its types, and the verses that Imam al-Tahawi spoke about abrogation in his book.